Cooling phase organic fertilizer applied in saline soil increase the content of soil macro-aggregates and aggregate-associated carbon - Hongmei Bai; Shuhui Chen; Yajie Li; Weimin Bao; Meiying Liu; Quanyi Suo (PLoS ONE, 2025)
Soil aggregate formation and stabilization are pivotal for remediating saline-alkali soils, but the potential of cooling-phase organic fertilizer (CPOF)—a transitional stage in composting—has been overlooked. This study systematically investigated the regulatory effects of CPOF on saline soil aggregate systems, focusing on two key objectives: (1) comparing the efficacy of CPOF with organic fertilizers from other composting phases (initial, thermophilic, matured) in enhancing macroaggregate proportion and stability; and (2) clarifying how CPOF’s unique organic components influence carbon speciation across aggregate size fractions. Our results demonstrated that CPOF outperformed other composting phases in improving soil physical properties and aggregate dynamics. It reduced soil bulk density by 18.5% and increased porosity by 22.3%, driven by three mechanisms: (1) dominant humification microorganisms (e.g., Actinobacteria) secreting extracellular polymeric substances (EPS) that bind soil particles; (2) a balanced ratio of labile and stable organic components, providing both immediate binding agents and long-term humic substances; and (3) enhanced microbial-mineral interactions via ligand exchange and cation bridging. In aggregate dynamics, CPOF significantly promoted macroaggregate (>0.25 mm) formation and stability, with peak effects at 180 days. This was attributed to fungal communities (e.g., Peniophora, Mucorales) producing glomalin-related soil proteins (GRSP) and calcium-mediated particle bridging. CPOF also increased organic carbon content in macroaggregates by 18–22% through labile carbon (supporting microbial activity) and transitional humic substances (facilitating long-term sequestration), with sustained stability over 540 days. These findings highlight CPOF as a time-sensitive amendment that synchronizes microbial activity with physical carbon protection, offering a scalable solution for saline soil rehabilitation. A proposed two-phase strategy—initial CPOF application for rapid improvement, followed by mature compost for long-term maintenance—could enhance carbon sequestration efficiency by 15–20% in regions like the Yellow River Basin, supporting climate-smart agriculture and global saline soil management.